Family Nursing Care for Family Members with Leprosy - Muniroh, Siti; Pujiani, Pujiani; Ani, Zuli; Kusumaningrum, Anisa (Universitas Muhammadiyah Lamongan, 2022)
Introduction: Leprosy is a highly contagious disease. If there is someone who suffers from severe leprosy and is not treated properly, at any time the leprosy bacteria will spread into the air and most likely will spread to the people around him. economy, environment, and others. This study aimed to provide nursing care to a family member who suffers from leprosy.Methods: This research design uses a literature study from four families using 3 scientific papers. The nursing process includes assessment, diagnosis, intervention, implementation, and evaluation. Assessment of leprosy clients found that the main complaint was the presence of raised patches accompanied by a feeling of heat, and black spots on the legs.Results: Priority nursing diagnoses in family 1, non-compliance related to the impact of sick family members, family 2 and 3, knowledge deficit related to the inability of the family to recognize health problems and family 4, non-compliance related to the inability of the family to recognize family health problems. Nursing interventions that exist in theory and real cases have similarities and differences, where the plans in each nursing diagnosis are adjusted to the client's condition and facilities and infrastructure.Conclusion: Implementation was adjusted to the cooperation between the client, family, nurse and health services. Evaluation of nursing care in family 1 is resolved and the intervention is discontinued Nurse must give health education for leprosy and monitor health efforts in each family.